(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper considers the topic of neuroscience and how it affects the courtroom. Indeed neuroscientific findings, on the one hand, may constitute new procedural evidence, often used in criminal trials, and, on the other, pose new challenges to the protection of human rights.